Pengaruh Brand Image, Digital Marketing, dan Celebrity Endorsement Terhadap Keputusan Pembelian Produk XYZ di DKI Jakarta - Marpaung, Rachel Angelica Putri; Santoso, Siswanto Imam; Setiyawan, Hery (Universitas Galuh, 2025)
Purchasing decisions is a process that consumers go through in selecting and buying a product after considering various alternatives that can be influenced by several factors, such as brand image, digital marketing, and celebrity endorsement. The purpose of this study is to analyze the partial and simultaneous influence of brand image, digital marketing, and celebrity endorsement on consumers purchasing decision of XYZ in Jakarta. This research was conducted online in November – December 2024. A descriptive survey method with a quantitative approach was employed, with a purposive sampling of 120 respondents determined using the Lemeshow formula, allowing for a 9% margin of error. Data was collected using a close-ended questionnaire with a Likert scale, distributed online via Google Forms though Instagram and X. The analytical tools used in this research is IBM SPSS Statistics. This study indicate that brand image has a significant and positive influence on purchasing decisions, as shown by a regression coefficient of 0.463, a t-value of 3.411 (>1.98), and a significance level of 0.001 (<0.05). Digital marketing has a positive bun insignificant influence on purchasing decisions, as shown by a regression coefficient of 0.123, a t-value of 0.718 (<1.98), and a significance level of 0.474 (>0.05). Celebrity endorsement has a significant and positive influence on purchasing decision, as indicated by a regression coefficient of 0.426, a t-value of 4.467 (>1.98), and a significance level of 0.000 (<0.05). Brand image, digital marketing, and celebrity endorsement have a simultaneous influence of 47,5%, as shown by the F-test significance level of 0.000 (<0.05) and an Adjusted R2 value of 0.475.